Platelet alloimmunization in transfusion-dependent thalassemia patients from Southern China (2014-2023) - Huang, Yuchen; Chen, Yuxi; Mo, Qiuhong; Mo, Huihui; Lu, Fang; Li, Hengcong; Li, Lilan; Chen, Jierun; Jiang, Lihong; Zhou, Yan; Zhong, Zhoulin (Frontiers in Immunology, 2025)
Patients with transfusion-dependent thalassemia (TDT) are at high risk of alloimmunization. While previous research is predominantly focused on red blood cell alloimmunization, the potential risks of platelet alloimmunization are frequently underestimated. We conducted a retrospective study of 249 TDT patients who underwent platelet immunology testing between January 2014 and December 2023 at Nanning Blood Center. Flow cytometry was used for platelet antibody screening, followed by enzyme-linked immunosorbent assay for detailed platelet antibody identification. Among the 249 TDT patients, 103 were detected positive for platelet alloimmunization (41.37%). Patients older than 12 had a higher prevalence of platelet alloimmunization than those younger than 12 (54.17% vs. 36.16%, P=0.009). Most of the platelet antibodies were human leukocyte antigen (HLA) antibodies alone (79.61%). Two TDT patients received cross-matched platelets and demonstrated successful transfusion responses with 24-hour corrected count increment being 10.62 and 7.80, respectively.TDT patients demonstrate a high prevalence of platelet alloimmunization, characterized by a diverse array of antibodies, predominantly HLA antibodies. In conclusion, proactive screening for platelet antibodies and employing cross-matched platelet transfusions can mitigate alloimmunization risks in TDT patients and address the clinical challenge of platelet transfusion refractoriness.